2017
DOI: 10.3892/br.2017.1024
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular characteristics of chronic fatigue syndrome

Abstract: Abstract.Patients with chronic fatigue syndrome (CFS) commonly exhibit orthostatic intolerance. Abnormal sympathetic predominance in the autonomic cardiovascular response to gravitational stimuli was previously described in numerous studies. The aim of the current study was to describe cardiological and clinical characteristics of Italian patients with CFS. All of the patients were of Caucasian ethnicity and had been referred to our center, the Cardiology Department of the University Hospital of Pavia (Pavia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 25 publications
0
15
0
3
Order By: Relevance
“…Approximately half of patients with ME/CFS also appear to have a previously undiagnosed medical condition, most often diabetes, cardiovascular disease, and thyroid diseases (Maloney et al, 2009). Few studies have investigated the possible associations between MetS and ME/CFS (Maloney et al, 2009;Naviaux et al, 2016;Germain et al, 2017;Bozzini et al, 2018). It was first suggested that patients with ME/CFS were twice as likely to have MetS compared with controls, after adjusting for body mass index, waist circumference, triglycerides, and glucose levels (Maloney et al, 2009).…”
Section: Me/cfs Association With Metabolic Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Approximately half of patients with ME/CFS also appear to have a previously undiagnosed medical condition, most often diabetes, cardiovascular disease, and thyroid diseases (Maloney et al, 2009). Few studies have investigated the possible associations between MetS and ME/CFS (Maloney et al, 2009;Naviaux et al, 2016;Germain et al, 2017;Bozzini et al, 2018). It was first suggested that patients with ME/CFS were twice as likely to have MetS compared with controls, after adjusting for body mass index, waist circumference, triglycerides, and glucose levels (Maloney et al, 2009).…”
Section: Me/cfs Association With Metabolic Diseasementioning
confidence: 99%
“…Dysautonomia including postural orthostatic tachycardia syndrome may be present in many patients with ME/CFS (Hollingsworth et al, 2010) and could also explain other ME/CFS symptoms, such as fatigue, vertigo, decreased concentration, tremors, and nausea (Bozzini et al, 2018). Interestingly, the low systolic blood pressure observed in ME/CFS patients is usually accompanied by exaggerated diurnal variation, which is inversely correlated with increasing fatigue (Davis et al, 2000;Newton et al, 2009).…”
Section: Me/cfs Association With Metabolic Diseasementioning
confidence: 99%
“…This suggests contribution of RR interval dynamics, an electrocardiogram parameter or autonomic nervous system activity during non-REM sleep to disrupted sleep in ME/CFS patients [ 27 ]. Additional studies have shown the potential role of cardiovascular regulation in the pathomechanism of ME/CFS [ 27 , 55 ]. ME/CFS patients presented with increased heart rate, and reduced heart rate variability.…”
Section: Discussionmentioning
confidence: 99%
“…Psychiatric morbidities, including chronic fatigue syndrome, were also reported in patients who recovered from SARS [100]. Given the strong association between psychiatric conditions, such as depression and chronic fatigue syndrome, and CVD, such as chronic HF and cardiac arrhythmias, the evidence backing long-term CV sequelae of these infections appears compelling [101][102][103][104].…”
Section: Future Complications and Implicationsmentioning
confidence: 99%